Characterization of muscle recruitment during gait of bilateral transfemoral and through-knee persons with limb loss - Benton, Alice M.; Amiri, Pouya; Henson, David P.; Sivapuratharasu, Biranavan; Mcgregor, Alison H.; Bull, Anthony M. J. (Frontiers in Bioengineering and Biotechnology, 2023)
Due to the loss in musculoskeletal capacity, there is an increased burden on the residual limbs of bilateral trans-femoral and through-knee persons with limb loss. This reduced capacity is associated with an increased cost of walking that is detrimental to functionality. Compensatory gait strategies are adopted by this population, however, how these strategies relate to specific muscle recruitment is not known. The primary aim of this study is to characterize muscle recruitment during gait of this population. The secondary aim is to assess whether the measured kinematics can be actuated when the endurance of specific muscles is reduced, and if this is the case, which alternative muscles facilitate this. 3D gait data and high-resolution magnetic resonance images were acquired from 6 bilateral trans-femoral and through-knee persons with limb loss. Subject-specific anatomical muscle models were developed for each participant and a validated musculoskeletal model was used to simulate the quantification of muscle forces in two conditions: during normal gait (baseline), and when muscles, which were identified as functioning above a ‘healthy’ level at baseline, have a reduced magnitude of maximum force capacity (reduced endurance). To test the hypothesis that there are differences in muscle forces between the baseline trials and the simulations with reduced muscular endurance, a Bonferroni corrected two-way ANOVA with repeated measures was completed between the two states. The baseline analysis showed that the hip flexors experience relatively high muscle activations during gait. The reduced endurance simulation found two scenarios, firstly for 5 out of the 12 simulations the baseline kinematics could not be reproduced with the reduced muscular capacity. Secondly, for the 7 out of 12 cases where the baseline kinematics were achieved, this was possible with compensatory increased activation of some muscles with similar function (p≤0.003). Evidently, due to the loss of the ankle plantar flexors, gait imposes a high demand on the flexor muscle group of the residual limb. This study highlights how the elevated cost of gait in this population manifests in muscle recruitment. To enhance functionality it is critical to consider the mechanical demand on the hip flexors and to develop rehabilitation interventions accordingly.